Duszpasterska troska o ojców rodziny - Śmigiel, Wiesław (Verbum vitae, 2011)
In the Church’s teaching fatherhood is defined as a vocation and constitutes an element of family life that is significant and difficult to replace. However, social changes and contemporary problems connected with the functioning of family have lead to a modification of the father model, and even the thesis about its crisis has appeared. This is why pastoral care for fathers of the family is one of the priorities of the family pastorate. Creating structures and methods of such a pastorate is a pastoral postulate. It is worth returning to the practice of special teachings for fathers as well as establishing workshops, retreats, pilgrimages and other forms of work with fathers. Experiences of Catholic families associations that give broadly understood support to fathers are especially valuable, as well as the grass-roots Inicjatywa Tato.Net that actively promotes responsible fatherhood.